Temperature dependence of threshold stress for aluminum-based materials exhibiting high strain rate superplasticity - Kum, D.; Frommeyer, G. (Korean Institute of Metals and Materials, 1997)
High strain rate superplasticity has been mostly demonstrated in aluminum-base powder metallurgy materials. The superplasticity has been illustrated by incorporating threshold stress, which decreases apparent flow stress, and is commonly interpreted as an extension of usual fine-grain superplasticity. That is, majority of deformation takes place in grain boundaries, meaning grain boundary sliding is the governing mechanism. Dispersion particles or whiskers seem to cause the threshold stress, whose value shows strong temperature dependence. In order to understand the exact nature of the temperature dependence, threshold stress data appeared in literature has been reanalyzed using linear and exponential functions of temperature. The modulus-compensated threshold stress data fit well with the Arrhenius plot, and two modes of thermally activated process are suggested. One is dominant at lower temperature ranges, and has an activation energy of about 50 kJ/mole and an interaction between moving dislocations and particles or interfaces is considered as the origin of the threshold stress. Another one is operational at very high temperatures near incipient melting condition, which exhibits considerably higher activation energy. Referring to the high activation energy and serrated flow curves, solute drag against gliding dislocations has been suggested as a possible source for the second threshold stress.